Angiogenesis in Inflammatory Bowel Disease - Canan Alkim; Huseyin Alkim; Ali Riza Koksal; Salih Boga; Ilker Sen (Hindawi Limited, 2015)
Angiogenesis is an important component of pathogenesis of inflammatory bowel disease (IBD). Chronic inflammation and angiogenesis are two closely related processes. Chronic intestinal inflammation is dependent on angiogenesis and this angiogenesis is modulated by immune system in IBD. Angiogenesis is a very complex process which includes multiple cell types, growth factors, cytokines, adhesion molecules, and signal transduction. Lymphangiogenesis is a new research area in the pathogenesis of IBD. While angiogenesis supports inflammation via leukocyte migration, carrying oxygen and nutrients, on the other hand, it has a major role in wound healing. Angiogenic molecules look like perfect targets for the treatment of IBD, but they have risk for serious side effects because of their nature.